Data for: Growing faster, longer or both? Modelling plastic response of Juniperus communis growth phenology to climate change - Tumajer, Jan; Buras, Allan; Camarero, Jesús Julio; Carrer, Marco; Shetti, Rohan; Wilmking, Martin; Altman, Jan; Sangüesa-Barreda, Gabriel; Lehejček, Jiří (Dryad, 2021)
Aim: Plant growth and phenology plastically respond to changing climatic
conditions both in space and time. Species-specific levels of growth
plasticity determine biogeographical patterns and the adaptive capacity of
species to climate change. However, a direct assessment of spatial and
temporal variability in radial-growth dynamics is complicated, as long
records of cambial phenology do not exist. Location: 16 sites across
European distribution margins of Juniperus communis L. (the Mediterranean,
the Arctic, the Alps and the Urals). Time period: 1940-2016 Major taxa
studied: Juniperus communis Methods: We applied the Vaganov-Shashkin
process-based model of wood formation to estimate trends in growing season
duration and growth kinetics since 1940. We assumed that J. communis would
exhibit spatially and temporally variable growth patterns reflecting local
climatic conditions. Results: Our simulations indicate regional
differences in growth dynamics and plastic responses to climate warming.
Mean growing season duration is the longest at Mediterranean sites and,
recently, there is a significant trend towards its extension of up to 0.44
days per year. However, this stimulating effect of longer growing season
is counteracted by declining summer growth rates caused by amplified
drought stress. Consequently, overall trends in simulated ring-widths are
marginal in the Mediterranean. By contrast, durations of growing seasons
in the Arctic show lower and mostly non-significant trends. However,
spring and summer growth rates follow increasing temperatures, leading to
a growth increase of up to 0.32 % per year. Main conclusions: This study
highlights the plasticity in growth phenology of widely distributed shrubs
to climate warming–an earlier onset of cambial activity that offsets the
negative effects of summer droughts in the Mediterranean and, conversely,
an intensification of growth rates during the short growing seasons in the
Arctic. Such plastic growth responsiveness allows woody plants to adapt to
the local pace of climate change.
This data package contains (i) input ring-width series of Juniperus
communis used to calibrate the Vaganov-Shashkin model and (ii) outputs of
the model important for the interpretations made in the above-referenced
paper. (i) were obtained using standard dendrochronological procedures
(including field sampling, laboratory processing and ring-width
measurement). Individual datasets are stored in RWL format which might be
uploaded by most of dendrochronological softwares. Data represent annual
ring widths of J. communis shrubs. If multiple discs/radii were measured
at specific site, they were averaged into the shrub level. One RWL file is
provided for each site of the network. (ii) represent outputs of the
Vaganov-Shashkin models' simulations applied on each site of the
network. For detailed description of each dataset, please, see enclosed
###README.txt file.
Site codes The data are related to 16 analyzed sites spread across the
European part of J. communis distribution. For the full spatial
identification (coordinates), please, see Figure 1 in the above-referenced
paper. The site codes are used as follows: ARCTIC SITES ABI = Abisko
(Sweden) FIN = Finse (Norway) KEV = Kevo (Finland) KIR = Kirkenes (Norway)
KOB = Kobbefjord (Denmark, Greenland) URAL SITES PUR = Polar Ural NUR =
Northern Ural SUR = Southern Ural (all Russia) ALPINE SITES CDL = Croda de
Lago SEL = Sella Nevea RHE = Val di Rheme VEN = Val Ventina (all Italy)
MEDITERRANEAN SITES ALI = Aliaga (Spain) PEN = Penarroya (Spain) POL =
Pollino (Italy) VIL = Villarroya de los Pinares (Spain) Ring-width series
of J. communis Folder 'OBSERVATION' contains raw (non-detrended)
ring-width series for each sampled shrub. For sites, where multiple radii
and/or cross-sections were measured, individual raw measurements were
averaged to the level of individual shrubs. Data are stored in standard
format RWL which can be loaded by most of dendrochronological programs
(including the dplR package for R). One RWL file is presented for each
site. Simulated daily growth rates Daily growth rates simulated by the
VS-model are stored in 'SIMULATION-Growth Rates' subfolders.
Simulated integral growth rates and partial growth rates to temperature
have a format of a semicolon-separated matrix. The first row of the matrix
represents a header. Each of the 365 rows indicates simulated growth rates
for specific DOY (starting with DOY 1 in the first row and DOY 365 in the
last row). Columns indicate individual calendar years of simulations
(starting with the year 1940 in the first column). Because partial growth
rates to photoperiod are invariant from year to year, the respective
matrix is simplified to 365 rows and 1 column. Simulated number of
differentiated cells Numbers of differentiated cells since the beginning
of the calendar year are for each day stored in the 'SIMULATION-Cell
differentiation' folder. Individual files have a format of a
semicolon-separated matrix. The first row of the matrix represents a
header. Each of 365 rows indicates the numbers of differentiated cells
since the beginning of the growing season for each DOY (starting with DOY
1 in the first row and DOY 365 in the last row). Columns indicate
individual calendar years of simulations (starting with the year 1940 in
the first column). Simulated cambial phenology Key dates of simulated
cambial phenology are stored in the 'SIMULATION-Phenology'
folder. Each file contains a semicolon-separated table with 3 columns. The
first one indicates the calendar year, the second one simulated DOY of
cambial activity onset and the last one simulated DOY of cambial activity
cessation. Simulated site chronologies Simulated site chronologies are
stored in the 'SIMULATION-Chronology' folder. Each file contains
a semicolon-separated table with 2 columns. The first one indicates the
calendar year, the second one value of the simulated chronology.
Keywords: FOS: Biological sciences; Dendrochronology; growing season; juniper; process-based model; Phenology; shrub; Vaganov-Shashkin model